An Alarming Lack of Feeling: Urban Travel, Emotions, and British National Character in Post-Revolutionary Paris - Thompson, Victoria (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 2014)
This article analyzes British narratives of voyages made to Paris during three periods: the Peace of Amiens (March 1802 to May 1803), the first Restoration (April 1814 to May 1815), and in the first few years of the second Restoration (June 1815 to ca. 1820). These accounts reveal a consistent use of strong and distressing expressions of emotion when describing locations in the city associated with the events of the French Revolution. An analysis of these “emotional landmarks” allows us to understand the role of trauma in unsettling distinctions between the British and French in the aftermath of the Revolution. It also demonstrates that travel writers participated in an emotional community consistent with the nation, one that used these emotional landmarks to establish a new distinction between the two national characters based on emotion.